TREN PENELITIAN DAN PENGEMBANGAN PENDIDIKAN KARAKTER: ANALISIS KONSEPTUAL DAN STUDI EMPIRIK - Hasanah, Tita; Amita, Nindy (Prodi PGMI IAI Sahid, 2026)
Character education is a fundamental aspect in shaping students' personalities with morals, ethics, and integrity. One approach considered effective in developing character education systematically and based on evidence is research and development (R&D). This article aims to examine the role of research and development in character education, examine relevant R&D models, and map empirical findings of character education research based on scientific publications. The methods used are literature study and document analysis utilizing the Scopus database. The search was conducted using keywords related to research and development and character education, resulting in 2,673 published documents from 1971–2025. The results of the study indicate that research and development in character education is growing rapidly, with the United States and Indonesia as the most productive countries. Various R&D products developed include character education models, modules, assessment instruments, and technology-based learning media. However, research and development in character education still faces challenges, particularly in objective character measurement and consistent implementation across institutions. Therefore, methodological innovation and strengthening assessment instruments are essential to improve the effectiveness of character education in the future.